Knowledge Management Capability in Nepalese Commercial Banks - Bhandari, Dilliram (Management Dynamics, 2020)
This study focuses on exploring the state of knowledge management capability (KMC) in Nepalese commercial banks and develop as well as validate its dimensions. A survey research strategy was adopted to achieve the study objective and the descriptive research design was followed to explore the state of KMC in Nepalese commercial banks. The population of this study was comprised of all 27 commercial banks of Nepal. To achieve sufficient sample size and generalization of the result, the sample frame for this study included 9 commercial banks. At least 20 employees from each organization were approached to respond about the existence of KMC in their respective organizations. Altogether 250 questionnaires were distributed, out of this 180 questionnaires were returned, the response rate was 72%, which may be taken highly satisfactory in survey research design. The exploratory factor analysis (EFA) of KMC was done to extract the latent factors or dimensions from the measured items. All three dimensions of KMC were found in unsatisfactory state. The private sector banks were found to have a better position in all three dimensions of KMC than the public sector banks. Further, the EFA of KMC items revealed for dimensions of KMC: knowledge acquisition, knowledge sharing-employees, knowledge sharing-management and knowledge utilization.